ANALISIS KEMAMPUAN PASSING BAWAH BOLA VOLI DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) PADA PESERTA DIDIK SMKN H MOENADI - Muthoharoh, Layly; Setiyawan, Setiyawan; Santoso, Teguh (Journal of Physical Activity and Sports (JPAS), 2025)
The purpose of this research is to determine the ability to pass under volleyball using the teaching at the right level (TaRL) approach for students at SMKN H MOENADI. The research method used is quantitative descriptive. The data used in this research was collected using tests. The population in this study were 35 students of class The results of the research show that the test results after being given the TaRL approach have increased with the data obtained by 8 students with a percentage (23%) who had lower passes in the very good category, 11 students with a percentage (31%) who had lower passes in the good category. , 12 students with a percentage (34%) who have lower passes in the medium category, 3 students with a percentage (9%) who have lower passes in the poor category, 1 student with the percentage (3%) who had a lower pass was in the very poor category. From the research results, it can be concluded that there is an increase in volleyball bottom passing ability with the teaching at the right level (tarl) approach in students at SMKN H MOENADI, with an increase in the percentage of the excellent category from 17% to 23%, good from 14% to 31% , moderate from 31% to 32%, from less than 26% to 9%, and very less from 11% to 3%.